2002
DOI: 10.1002/hed.10092
|View full text |Cite
|
Sign up to set email alerts
|

Swallow function and perception of dysphagia in patients with head and neck cancer

Abstract: Patients were able to perceive decrements in their swallowing function as dysphagia and may have limited their oral intake in response to that perception. The ability to accurately perceive swallowing function may be useful for self-monitoring changes in dysphagia status during a course of swallow therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 39 publications
9
119
0
5
Order By: Relevance
“…Objective evaluation of swallowing correlated with some of the patients assessed symptoms. This has been described previously: Pauloski et al [27] made repetitive VF measurements in 132 patients and asked, ''Do you experience problems with swallowing?'' at the same time points.…”
Section: Discussionmentioning
confidence: 99%
“…Objective evaluation of swallowing correlated with some of the patients assessed symptoms. This has been described previously: Pauloski et al [27] made repetitive VF measurements in 132 patients and asked, ''Do you experience problems with swallowing?'' at the same time points.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with head and neck cancer undergoing surgery have a high incidence of postoperative complications (anastomotic fistula, wound infections, and major complications such as septicemia) (Arriraga et al, 1990) and have several problems related to swallowing function and perception of dysphagia (Pauloski et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, restrictions in oral intake have been previously associated with videofluoroscopic measures of reduced laryngeal excursion, reduced cricopharyngeal opening, and evidence of aspiration and/or residue [33]. In the current study, descriptive analysis revealed that the pharyngeal and crico-esophageal phases were impaired with slightly higher frequency in the CRT group, which may have resulted in greater texture restriction, perceived need for supplemental feeding and overall inferior functional swallowing.…”
Section: Resultsmentioning
confidence: 55%